APLIKASI ALGORITMA PRIM UNTUK MENENTUKAN MINIMUM SPANNING TREE SUATU GRAF BERBOBOT DENGAN MENGGUNAKAN PEMROGRAMAN BERORIENTASI OBJEK - Nugraha, Deny Wiria (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2011)
In this study, the algorithm used is Prim’s algorithm—an algorithm in graph theory to seek a minimum spanning tree for a weighted connected graph. The program used is a program created with Delphi 7 programming language used for searching the minimum spanning tree of a graph model with the weight of each form of distance/length connecting the points/vertices. Then display the information search process sequence of minimum spanning tree, the total number of minimum length and the resulting computing time to determine the efficiency of Prim’s algorithm. Based on the results of research, Prim's algorithm computation time in finding the minimum spanning tree of a weighted graph will grow up along with increasing the number of points/vertices and the number of sides of the weighted graph. Keywords:Prim’s Algorithm, Graph model, Minimum Spanning Tree